(untitled) (Semiárida, 2020)
Eight broods of sukling pigs were raised from birth to 56th days old. Two diets were compared with four broods each one; as follows: "A" maternal milk until 56 days, and "B" maternal milk until 42 days (weaning time came forward 14 days due two problems with two of the broods) plus liquid milk substitute from day 7th to 56th. It was added pre-initiation food to both treatments from day 14th to 56th.The daily weight gains and average weights did not show statistical difference (P 0,05). The lack of significance between day 42th to 56th demonstrate that milk substitute has not negative effects. The intake of pre-initiation food resulted with not statistical difference during the 14-42 days period; although a difference of 260 g. per suckling pig was observed on account of diet "B". The average weight of sows did not show statistical differences (p 0,05), however a 16,75 days shortening of newborn conception period was observed for sows of diet "B".